Deep Magma Storage Revealed by Multi-Method Elemental Mapping of Clinopyroxene Megacrysts at Stromboli Volcano - Ubide, Teresa; Caulfield, John; Brandt, Claire; Bussweiler, Yannick; Mollo, Silvio; Di Stefano, Flavio; Nazzari, Manuela; Scarlato, Piergiorgio (Frontiers in Earth Science, 2019)
The magmatic architecture and physicochemical processes inside volcanoes influence the style and timescale of eruptions. A long-standing challenge in volcanology is to establish the rates and depths of magma storage and the events that trigger eruption. Magma feeder systems are remarkably crystal-rich, and the growth stratigraphy of minerals sampled by erupted magmas can reveal a wealth of information on pre-eruptive processes. Here we combine detailed textural and chemical data acquired on large (>5 mm), euhedral augite megacrysts from Roman era activity (Pizzo scoria cone, 2.4-1.8 ka) at Stromboli (Italy) to investigate the plumbing system prior to the onset of current steady-state activity. Our dataset includes novel laser ablation time-of-flight mass spectrometry (LA-ICP-TOFMS) maps, which rapidly visualise multi-element zoning patterns across entire megacryst sections. The clinopyroxene data are complemented with geochemical constraints on mineral and melt inclusions, and adhering glassy tephra. Megacrysts are sector and oscillatory zoned in trace elements, yet their major element compositions are relatively uniform and in equilibrium with shoshonite-buffered melts. Mild sector zoning documents dynamic crystallisation under conditions of low undercooling during magma residence and growth. Clinopyroxene-melt thermobarometric and hygrometric calibrations, integrated with thermodynamically derived equilibrium equations, accurately track the P-T-H2O path of magmas. The refined models return restricted crystallisation depths that are deeper than those reported previously for historical and current eruptions, but consistent with deep clinopyroxene-dominated crystallisation (≥10 km), resembling other water-rich alkaline mafic systems. Megacryst cores are overgrown by oscillatory zoned mantles recording continuous input of magma that failed to trigger eruption. Crystal rims are characterised by a mild increase in compatible transition metals Cr and Ni, and depletion in incompatible elements, indicative of pre-eruptive mafic replenishment and magma mixing. The volcanic system appears to have been dominated by protracted periods of replenishment, convection and crystal residence, punctuated by rapid megacryst evacuation and eruption upon arrival of more mafic magma (days-weeks). Since the inception of current steady-state activity, eruption-triggering melts have become appreciably more mafic, suggesting that intrusion of primitive magma may be a key driver of the steady-state regime.